Evaluasi Proses Tata kelola Keamanan Informasi Menggunakan COBIT 5 Dengan Proses APO13, DSS04 dan DSS05 (Studi Pada DISKOMINFO Kabupaten Sidoarjo) - Ridho Hardiansyah; Yusi Tyroni Mursityo; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Department of Communication and Information (DISKOMINFO) of Sidoarjo Regency is a government agency that has the task of helping the regent doing the government affairs in the fields of communication, informatics, statistics and coding. In carrying out their duties, DISKOMINFO provides a data center (DC) that will be used to collect application data from each Regional Apparatus Organization (OPD) in Sidoarjo Regency to become a centralized storage area. The data center management process is carried out in the Information and Communication Technology Sector. Lots of data to be processed and possible threats to cyber attacks and data theft, so the need for good information security governance in order to improve data security and business continuity. To determine the ability of information security management it is necessary to evaluate the current condition data center of DISKOMINFO. This research uses the framework of Control Objective for Information and Related Technology (COBIT 5) using the APO13 (Manage Security), DSS04 (Manage Continuity) and DSS05 (Manage Security Services). From the results of the research, the level of maturity of the process managing information security at the data center for each process reaches level 1, with the value of the process of APO13 (64.29%), DSS04 (63.33%) and DSS05 (82.14%), the target level of expectations to be achieved are level 3, so there is a gap of 2 levels of all the processes. The recommendations from the results of the research that can be applied to improve the process of information security management in the data center at DISKOMINFO Sidoarjo Regency are four recommendations for the process of APO13, three recommendations for the process of DSS04 and seven recommendations for the process of DSS05.